Performance analysis in sport games - methodological approach - Milanovic, D.; Sporis, G.; Jukic, I.; Vuleta, D.; Simek Salaj, S. (World Congress of Performance Analysis of Sport VIII, 2008)
Adequate research methods and procedures have provided insights and findings which, on the one hand, have confirmed that it is feasible to scientifically analyse situation efficiency in sport games, and on the other, the obtained findings have been built in the sport games training technologies thus strongly contributing to reputation of Croatian basketball, football, volleyball, handball and waterpolo in the world. Certain approaches to scientific research on sport games, in which Croatian athletes have achieved remarkable results, have been presented in the article. In future, further advances in performance measurement systems are expected, aimed at better registration and analysis of situation efficiency parameters and its influence to final match outcome. Enabling the obtained findings and inferences to be integrated in everyday practice of sport games should improve training effects and competition results.